Capital Structure of Islamic Banks In Indonesia A Pecking Order Theory Perspective - Muliyani, Muliyani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This study aims to analyze the factors influencing the capital structure of Islamic banks in Indonesia. The research data was obtained from the financial reports of Sharia-based banks during the 2019-2023 period, which were uploaded on the official website www.idx.com. This study examines the effect of profitability (X1), sales growth (X2), and liquidity (X3) on capital structure using the panel data regression method. Based on the panel data estimation method, it was found that the Fixed Effects Model (FEM) is the most appropriate and shows that the three variables simultaneously influence capital structure decisions, with a significance value of 0.000 (less than 0.05). The implication is that corporate financial managers need to consider profitability, liquidity, and earnings growth before making financing-related policies. These three factors work simultaneously, ultimately determining how optimally banks and companies can benefit from each other—from efficient financing to controlled risk. A well-planned financing policy will ensure maximum benefits for all parties involved.